PENGARUH LITERASI ZIS DAN KEPERCAYAAN TERHADAP KEPUTUSAN SALURAN ZIS MELALUI PEMBAYARAN DIGITAL PADA LAZISMU KOTA MAKASSAR - Japar, Rahayu; Wahab , Abdul (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2024)
Zakat, Infaq, and Sadaqah (ZIS) not only constitute an obligation for Muslims but also play a crucial role as an alternative source of state financing, capable of stimulating economic activities and enhancing individual purchasing power. The distribution of ZIS acts as a balancing instrument in the financial economic sector of society, referred to as al-maliyah al-ijtima'iyah, which supports communal welfare. This study aims to examine the influence of ZIS literacy and trust levels on the use of digital payment methods for the distribution of ZIS. A quantitative approach is employed, with respondents comprising mustahik from Lazismu Makassar, as well as muzakki and munfiq who utilize digital payments. Data is gathered through questionnaires and analyzed using tests for convergent validity, discriminant validity, composite reliability, and structural model evaluation. The findings indicate that ZIS literacy has a positive and significant effect on the decision of muzakki and munfiq to channel ZIS through digital payments, with an original sample value of 0.325 and a P-value of 0.000. Trust is also found to have a positive and significant impact on the use of digital payment for ZIS distribution, with an original sample value of 0.647 and a P-value of 0.000. Both trust and ZIS literacy play essential roles in enhancing the use of digital payments, facilitating the distribution process, and strengthening the effectiveness of ZIS collection. The study concludes that improving ZIS literacy and trust in zakat management institutions can encourage more muzakki and munfiq to adopt digital payment methods, thereby supporting efficient ZIS management and maximizing the positive impact on community welfare.